Analisis Kesulitan Belajar Akibat Gangguan Perkembangan pada Siswa Kelas 6 di SDN Lidah Wetan II/462 - Rahma Rizky Ananda Sugiharto; Faizah, Zhafira Amalia Nur; Nabila Azahrotun Jihan; Grecia Bekti Ananta; Adellia Al Muhanif (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Education is a fundamental need for every individual to develop abilities and skills. Primary schools play an important role in developing students' basic abilities, skills and attitudes that will continue at the next level of education. However, there are still students who experience difficulties that ultimately have an impact on students' academic achievements. This study aims to identify the factors that cause learning difficulties in students at SD Negeri Lidah Wetan II/462. This research uses qualitative methods with interviews and observations of teachers and students. The results showed that students have difficulties in literacy, numeracy, and material comprehension. Low motivation, unsupportive environment, and lack of parental attention are some of the factors of learning difficulties. Teachers have an important role in overcoming these difficulties through individual approaches, remediation, enrichment, motivation and even observation. Some teachers also felt that there was a lack of support from either the government or the school in specialised training or mentoring to deal with learning difficulties due to developmental disorders. This research confirms that cooperation between teachers and parents is needed to overcome the problem of learning difficulties in students. With a deep understanding of the causes of learning difficulties, teachers can provide effective solutions to improve students' academic achievement.